Alimony for women working in Islamic law and Iraqi personal status law - Hogir. K. k. Mustafa (QALAAI ZANIST JOURNAL, 2021)
The phenomenon of women’s work has emerged as one of the features of contemporary social change. In our time, women are going out to work more than they were in ancient times, so they have become involved with men in more work. If a woman has a profession that requires her to spend her day or part of it, or the night or part of it outside the home, and the husband is satisfied with this leaving and does not prevent her from working, is the wife entitled to the alimony? Is she demanding that part of her earnings (her salary) be allocated to the family budget for household and children’s expenses? The Forum This research is based on an introduction and three mothers, the reasons and reasons for choosing the topic, research questions, research objectives, research limits, research methodology, and research structure. In the first topic, I dealt with the definition of alimony, the evidence for its legitimacy, and the wisdom of its legislation. As for the second topic, it dealt with the issue of estimating alimony: is it calculated based on the condition of the husband or wife? In the third section I dealt with the subject of alimony limits and the entry of some items into alimony, including household goods and the doctor’s fee, or not. As for the fourth topic, it showed the alimony and the origin of the working wife by looking at the dispute over the husband’s insolvency of alimony, the husband’s alimony, or the alimony for the poor wife. In conclusion, the researcher presented the most important findings and recommendations that came out of the study.